If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2+8k=6k+6
We move all terms to the left:
2+8k-(6k+6)=0
We get rid of parentheses
8k-6k-6+2=0
We add all the numbers together, and all the variables
2k-4=0
We move all terms containing k to the left, all other terms to the right
2k=4
k=4/2
k=2
| 5.6=1.4n | | n=5.6/1.4 | | 7(3n+3)=-126 | | 9²=h | | 0=|7x+7| | | x=2.20x-16=4x+- | | -90=|5x-5| | | 5q+22=-3q+26 | | x=2.4(5x-4)=4x+ | | 2x+x^=100 | | 3(-8-5n)-4n=-157 | | h(5)=175(1.028)² | | 3(x+2)^2-6=0 | | 6=-12c-(12-2c)+12 | | 3/2x+1=5/4x+3 | | 3x-2^2=16 | | 0=8n/3 | | x-3^2=25 | | 6x+40=112 | | x+2^2=40 | | 2x-1^2=25 | | t/2-11=9 | | t/5+15=25 | | (D^2-2D^4-13D^3+38D-24D)y=0 | | 60=(x)/(x+10) | | R+10.11r=10.15 | | p+9=180 | | 1/3x-8=26 | | x+(9)=-15 | | 6w-6=4w | | 3/4s=9/20 | | 4^(-5x)=4^(-7x+14) |